Simulation And Experimental Studies Of Intake And Exhaust Tuning For Automotive Engine Low-End Torque Enhancement - Khoo, Aik Soon (2014)

(untitled)
Modern passenger car engines have been “down-sized” for improved fuel consumption, resulting in high speeds to obtain good performance. Consumers, however, are demanding improved low-end torque for improved drivability. The target engine; a 4 valve per cylinder, 1.6L engine with two intake cam profiles and 2 intake runner lengths, was modeled and correlated with measured engine performance characteristics (power, torque, etc.); and pressure traces from combustion chamber, intake and exhaust manifolds to establish the confidence level in the model's prediction. Enjin kereta penumpang moden telah "dikecilkan saiz" untuk penjimatan bahan api, maka memerlukan putaran enjin yang tinggi untuk mendapatkan prestasi yang baik. Pengguna lebih gemar memperoleh tork pada putaran enjin rendah untuk pemanduan yang lebih baik. Enjin yang dikaji mempunyai 4 injap pada setiap silinder, 1.6 liter kapasiti, 2 profil sesondol masukan dan 2 ruang masukan yang berlainan panjang.